The Effectiveness Combination of Azolla Liquid Organic Fertilizer and Eco Enzyme On The Growth And Yield of Green Mustard (Brassica Juncea L.) - Siti Nurwalida; Rahmad Jumadi (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
The nutritional needs of the community are largely met by nutrient-rich horticultural crops known as mustard greens. Purpose: This study aimed to examine how the development and yield of mustard greens (Brassica juncea L.) were affected by the combination of Azolla Liquid Organic Fertilizer (POC) and Eco-Enzyme. Methodology: A two-factor Randomized Block Design (RBA) with three replications and nine treatment combinations resulted in 27 experimental units (162 plants). The doses of Azolla POC (0 ml, 15 ml, and 30 ml/plant) and Eco-Enzyme (0 ml, 10 ml, and 15 ml/plant) were the first and second factors, respectively. Results: The findings of this study indicated that plant height, number of leaves, root length, fresh weight, and dry weight were all significantly affected by the combination of Azolla POC and Eco-Enzyme. Findings: This study shows the best treatment in the combination of A₁E₁ (15 ml POC Azolla + 15 ml Eco-Enzyme per plant) which provides the most optimal growth and yield compared to single treatments or controls. Novelty: The novelty of this study lies in the application of a balanced combination dose of POC Azolla and Eco-Enzyme to maximize the growth of green mustard plants organically. Originality: This study is seen from the absence of previous studies that specifically test the interaction of these two organic materials on green mustard plants in the Benjeng District, Gresik Regency. Conclusion: Conclusion of this study showed that the combination of moderate doses of POC Azolla and Eco-Enzyme proved to be the most effective in increasing the growth and yield of mustard greens and has the potential to be developed as a sustainable organic fertilization strategy. Type of Paper: experimental research paper.